Reflective practice strategies of pre-service English teachers during teaching practicum to promote professional development - Nuraeni Nuraeni; Yayu Heryatun (Universitas Syiah Kuala, 2021)
Reflective practice in pre-service language teacher education is required as a tool to critically evaluate the link between theory and practice as well as to explore the beliefs and practices of pre-service English teachers during the teaching practicum programs. This study was aimed to explore the strategies of reflective practice used by pre-service English teachers during their teaching practicum to promote professional development. A case study was adopted as a research design and reflective journals were employed to collect data. The participants involved were six pre-service English teachers who had joined teaching practicum at schools for three months. This study employed thematic analysis for analysing the data from reflective journals. The results revealed that three strategies of reflective practice were identified: recollection, reflection-in-action, and mentoring process. In each strategy, the participants reflected differently based on the learning experiences they had, the teaching situation they faced, the ability to make decisions, and the beliefs they possessed. Through these strategies, they learned how to develop their own theories of teaching, how to make various links between theory and practice, and how to develop the level of thinking, problem solving, and decision making. If these strategies are continuously conducted, they ultimately can develop their professionalism as teachers. This study implies that reflective practice can also be incorporated in the curriculum of pre-service teachers and not only during teaching practicum since it entails huge benefits for pre-service English teacher development.